2020
DOI: 10.1186/s12967-020-02655-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for severe COVID-19 in middle-aged patients without comorbidities: a multicentre retrospective study

Abstract: Background Information regarding characteristics and risk factors of COVID-19 amongst middle-aged (40–59 years) patients without comorbidities is scarce. Methods We therefore conducted this multicentre retrospective study and collected data of middle-aged COVID-19 patients without comorbidities at admission from three designated hospitals in China. Results Among 119 middle-aged patients without comorbidities, 18 (15.1%) developed into severe illness and 5 (3.9%) died in hospital. ARDS (26, 21.8%) and elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 46 publications
3
41
0
Order By: Relevance
“… 19 In another study, increased D-dimer (> 1 μg/mL) levels and hypoalbuminemia were identified as risk factors for disease severity in patients with COVID-19. 20 In our study, the median neutrophil counts on admission were significantly higher among patients with critical disease than among patients with mild or severe disease, and the median lymphocyte counts on admission were significantly lower in patients with critical disease. Additionally, the median CRP, procalcitonin, LDH, creatinine, D-dimer, and troponin levels were significantly higher among patients with critical disease.…”
Section: Discussionsupporting
confidence: 37%
“… 19 In another study, increased D-dimer (> 1 μg/mL) levels and hypoalbuminemia were identified as risk factors for disease severity in patients with COVID-19. 20 In our study, the median neutrophil counts on admission were significantly higher among patients with critical disease than among patients with mild or severe disease, and the median lymphocyte counts on admission were significantly lower in patients with critical disease. Additionally, the median CRP, procalcitonin, LDH, creatinine, D-dimer, and troponin levels were significantly higher among patients with critical disease.…”
Section: Discussionsupporting
confidence: 37%
“…In the literature, few articles have been published commenting on risk factors for severe COVID-19 patients without comorbidities, unfortunately impact of the detailed imaging findings on disease severity was not assessed in these studies. A multicenter study reported that higher neutrophil to lymphocyte ratio with higher D-dimer levels (> 1 µg/ml) on admission might be a potential and reliable predictor for severe progression [19].…”
Section: Discussionmentioning
confidence: 99%
“…The study indicated that patients with serve illness were more likely to have respiratory diseases (OR = 3.42 (1.89 to 6.11)), hypertension (OR = 2.66 (1.46 to 3.82)), and cardiovascular disease (OR = 3.44 (1.44 to 3.82)). Another study [ 144 ] analyzed the risk factors of death among COVID-19 patients. The study reported negative markers between COVID-19 infections and other chronic diseases, such as diabetes (33.31%), hypertension (35.16%), chronic kidney disease (17.87%), and diseases of the circulatory system (22.53%).…”
Section: The Study Taxonomymentioning
confidence: 99%
“…Therefore, to provide a precise and accurate prediction model, a patient’s history of other ailments (diabetes, liver, kidney, heart disease, etc.) must be taken into consideration in both the COVID-19 prediction and detection process [ 144 , 145 , 146 ]. High computational resources are required to build complex DL models, processing, and interpreting big data, compared to working with IoT devices.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%